Surgical treatment of esotropia and unilateral ptosis in a patient with Cornelia de Lange syndrome - Won Jae Kim (Yeungnam University Journal of Medicine, 2019)
Cornelia de Lange syndrome (CdLS) is a rare multisystemic disorder that is characterized by mental retardation, prenatal and postnatal growth retardation, limb anomalies, and distinctive facial features, which include arched eyebrows that often meet in the middle (synophrys), long eyelashes, low-set ears, small and widely spaced teeth, and a small and upturned nose. Ophthalmic manifestations include long eyelashes, nasolacrimal duct obstruction, myopia, ptosis, and strabismus. There has been no report of surgical treatment for esotropia and unilateral ptosis in patients with CdLS in Korea. I report a patient with CdLS who underwent surgical treatment for esotropia and unilateral ptosis with a good surgical outcome.